Luftsichel's Sign in the Diagnosis of Bronchopulmonary Carcinoma (Revista de Medicina Clinica, 2022)
Clinical snapshot on "Luftsichel's Sign in the Diagnosis of Bronchopulmonary Carcinoma" presented in volume 6 issue 3 of 2022 of Revista de Medicina Clínica.
Keywords: Luftsichel; atelectasis; bronchopulmonary carcinoma